2021
DOI: 10.3390/diagnostics11122298
|View full text |Cite
|
Sign up to set email alerts
|

MRI as a Tool to Assess Interstitial Cystitis Associated Bladder and Brain Pathologies

Abstract: Interstitial cystitis/bladder pain syndrome (IC/BPS) is a chronic, often incapacitating condition characterized by pain seeming to originate in the bladder in conjunction with lower urinary tract symptoms of frequency and urgency, and consists of a wide range of clinical phenotypes with diverse etiologies. There are currently no diagnostic tests for IC/BPS. Magnetic resonance imaging (MRI) is a relatively new tool to assess IC/BPS. There are several methodologies that can be applied to assess either bladder wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Widespread vs local neurological pain is important to acknowledge when assigning treatments and designing clinical trials, as treatment efficacy may differ substantially between patients with different pain profiles (Farrar et al, 2023). The use of a molecular-guided MRI to detect biomarkers of bladder wall permeability has been recently proposed as a potential diagnostic tool to help guide treatment and tailor it to the cohort of patients with urothelial dysfunction (Towner et al, 2021;Towner et al, 2020). Amniotic Bladder Therapy.…”
Section: The Latest Therapeutic Advances and Experimental Targetsmentioning
confidence: 99%
“…Widespread vs local neurological pain is important to acknowledge when assigning treatments and designing clinical trials, as treatment efficacy may differ substantially between patients with different pain profiles (Farrar et al, 2023). The use of a molecular-guided MRI to detect biomarkers of bladder wall permeability has been recently proposed as a potential diagnostic tool to help guide treatment and tailor it to the cohort of patients with urothelial dysfunction (Towner et al, 2021;Towner et al, 2020). Amniotic Bladder Therapy.…”
Section: The Latest Therapeutic Advances and Experimental Targetsmentioning
confidence: 99%
“…In addition, the authors reported on an association of urothelial defects with clinical symptom severity, highlighting urothelial dysfunction as a substantial part of the pathophysiology [15 ▪ ]. Furthermore, contrast-enhanced MRI may be used to detect bladder wall hyperpermeability [16].…”
Section: Introductionmentioning
confidence: 99%
“…Towner et al evaluated the current value of MRI and the latest methodical developments in evaluation of bladder function and report on a current study of their own group on the use of contrast-enhanced (CE-) MRI to access the bladder wall hyperpermeability as one important pathological parameter in IC/BPS. They conclude that MRI-based tests would be a good tool in routine diagnosis of IC/BPS and could provide valuable information for the development of new therapeutics [ 11 ].…”
mentioning
confidence: 99%